Developing sustainable workplace through leadership: Perspectives of transformational leadership and of organizational citizenship behavior - Cho, Cheng-Chung; Kao, Rui-Hsin (Frontiers in Psychology, 2022)
The objective of this study was to investigate the leadership style of the supervisor to develop the organization’s sustainable workplace of and the extra-role behavior of employees (ie., OCB). An organizational context of the immigration officer is explored, by using the data collected from a survey of 453 immigration officers from 26 immigration officer teams in Taiwan. This study has verified transformational leadership and organizational commitment that they have positive effect on organizational citizenship behavior (OCB) of immigration officers. Moreover, it showed that organizational climate has context effect on organizational commitment and OCB. Furthermore, the results of this study have shown that aggregated transformational leadership has cross-level interactions on OCB. This study also found that the transformational leadership has strong effect on organizational commitment and OCB. This study adopts a cross-level study taking organizational environmental factors and cross-level interactions as research considerations. Because of the focus on group level impact, the research methodology can apply the supervisor's leadership style and organizational climate to measure whether immigration officers have a high degree of organizational commitment and influence their OCB performance across levels. The organizational commitment of the immigration officers and their individual OCB performance could be improved by converging the organizational context effect of aggregated transformational leadership and organizational climate. This study found that the application of transformational leadership is extremely helpful for the organization to develop sustainable workplace and extra-role behavior of employees.